Optimalisasi Penggunaan Media Sosial oleh Kelompok Informasi Masyarakat untuk Desa Wisata Budaya Beji, Gunungkidul - Muhamad Muhamad; Adila Rafa Callysta; Audrey Nevtasha Bianca Putri; Fikar Ilya Rahman; Lucky Arif Darmawan; Teofilo Vincent Fernando Setiawan; Fikri Danang Himawan (Direktorat Pengabdian kepada Masyarakat, 2024)
Kelompok Informasi Masyarakat (KIM) is an independent and creative community communication institution that aims to form a network for information dissemination, encourage community participation in development, and enhance public intelligence in receiving information. However, the community still finds KIM's roles and functions somewhat unclear. The KKN-PPM UGM Unit Patuk team responded by assisting in creating social media accounts for each padukuhan and conducting a socialization program about KIM, covering its definition, roles, objectives, functions, social media management strategies, topics that can be posted or should be avoided, and Instagram algorithms. This study employs a qualitative approach with a focus on observation and interviews to understand the experiences and perceptions of KIM members regarding the use of social media as a tool for sharing information in the Padukuhan environment. The socialization materials include explanations about KIM according to Kominfo, the importance of spreading accurate information, and guidelines on what can and cannot be posted on social media. Additionally, we discussed the dangers of posting incorrect information, the use of Instagram, types of content that can be posted, and the best times to post according to social media algorithms. We also facilitated the creation of social media accounts for each padukuhan in Beji, choosing Instagram due to its popularity and features that effectively support information dissemination. KIM members from various dusuns showed high enthusiasm for this socialization and stated that they now better understand the main roles and functions of KIM, recognize its benefits as a tool to promote the potential of their dusuns through social media, master effective techniques for disseminating information on the platform, and have basic knowledge of social media design.